Pemberdayaan masyarakat melalui pengolahan teh dan kopi beras khas Ketan Hitam di Desa Latellang Kabupaten Bone - Andi Muhammad Irfan Taufan Asfar; Syarif Nur; Andi Muhamad Iqbal Akbar Asfar; Andi Hasryningsih Asfar; Andi Nurannisa; Eka Sudartik (Universitas Hamzanwadi, 2022)
Black glutinous rice is a potential commodity in Latellang Village. However, this potential is not empowered because there is no counseling or other service activities in processing black glutinous rice. The community, especially partners, namely the Maddaung Farmer Group, do not take full advantage of black glutinous rice and only process it into delicious snacks and served at certain times. Therefore, this community service aims to maximize the potential of black glutinous rice by diversifying processed black glutinous rice products into coffee and tea. This product has never existed or been introduced by extension workers or replicated other product innovations, especially in Bone Regency. Community empowerment through this community service program is carried out through three main stages: counseling, training, and mentoring. The results of the program implementation are that partners can find out information on the benefits of processing black glutinous rice and have skills in diversifying products into tea and coffee. In addition, partners have also been able to process finances and market products through the marketplace with an increase in productivity of 98%. The impact of this service can realize sustainable development goals, namely healthy and prosperous villages.